Adoption of food safety measures on milk production in Nepal: Impact on smallholders' farm-gate prices and profitability. (July 2017) - Kumar, Anjani; Thapa, Ganesh; Roy, Devesh; Joshi, P.K.
Highlights: We examined the status and drivers of milk safety measures practiced on dairy farms in Nepal. Estimated the cost of compliance and the impact of milk safety measures on farm-gate prices and dairy profitability. We found a positive impact of food safety measures on farm-gate milk prices. A positive effect of food safety measures on dairy profitability is also observed at the initial treatment level. Abstract: One way to ensure food safety is by enhancing compliance at the farm level. This study investigates the status, estimates the cost, identifies the determinants, and assesses the impact of compliance with food safety measures (FSM) in milk production in Nepal. The study is based on primary data collected from six high milk producing districts that captures the geographical and institutional diversity of milk production. Results show that the status of farm level compliance with FSM is not very encouraging. Also, the intensity of adoption of FSM exhibits significant inter- and intra-district variations. It varies positively with herd size but the additional cost of compliance with FSM varies negatively with herd size. Among other determinants, access to information, and incidence of inspection for conformity with safety and quality standards are also associated with higher adoption of FSM. Finally, we also estimate the impact of FSM on farm-gate prices and farmers' profits and conduct several robustness checks.